The role of mTOR pathway as target for treatment in adrenocortical cancer - Maria Cristina De Martino (Endocrine Connections, 2019)
Adrenocortical carcinomas (ACCs) are rare tumors with scant treatment options for which new treatments are required. The mTOR pathway mediates the intracellular signals of several growth factors, including the insulin-like growth factors (IGFs), and therefore represents a potential attractive pathway for the treatment of several malignancies including ACCs. Several mTOR inhibitors, including sirolimus, temsirolimus and everolimus, have been clinically developed. This review summarizes the results of the studies evaluating the expression of the mTOR pathway components in ACC s, the effects of the mTOR inhibitors alone or in combination with other drugs in preclinical models of ACCs and the early experience with the use of these compounds in the clinical setting. The mTOR pathway seems a potential target for treatment of patients with ACC, but further investigation is still required to define the potential role of mTOR inhibitors alone or in combination with other drugs in the treatment of ACC patients.